The Inventory of Aquatic Macroinvertebrates in Various Waterfall in East Region of Malang, East Java - Wijayanti, Erna; Fauzi, Ahmad; Widiansyah, Arindra Trisna; Mustofa, Zainul; Setyanto, Haqqi Anajili; Sukoco, Restu Megadiana; Nuha, Ulin; Fadilah, Rizka Elan (Proceeding International Conference on Global Resource Conservation, 2015)
Indonesia as Maritime Island has many water regions. Waterfall is one of the water region that has a large number of aquatic macroinvertebrates. The aim of this research is to collect and identify the various aquatic macroinvertebrates that can be found in several waterfalls in east Region of Malang, East Java. The research was carried out on September until November 2015 in six waterfalls: Coban Jahe, Coban Pelangi, Coban Trisula, Coban Kembar, Coban Ringin Gantung and Coban Pitu. Dragnet was used to collect the samplesof aquatic macroinvertebrates in some sampling point. The result of this research was found 38 families that belonged to 18 ordo in 6 different classes: Insecta, Oligochaeta, Gastropoda, Hirudinae, Turbellaria, and Crustacea. The information about the inventory of aquatic macroinvertebrates will give another suggestion for the local government to conserve this animals especially waterfall environment, not only as tourist area but also as a source of knowledge to do another research.Â Keywords: Aquatic macroinvertebrates; inventory; Malang; waterfalls